Moral minds: How and when does servant leadership influence employees to benefit multiple stakeholders? - Lemoine, G. James; Hartnell, Chad A.; Hora, Snehal; Watts, Daniel I. (Personnel psychology, 2024)
Servant leadership's unique focus on care and concern for multiple stakeholders has caught the attention of academic and practitioners alike. Its theoretical novelty, however, remains underutilized as a means to contribute unique insights to the leadership literature. We draw on servant leadership's moral foundation—utilitarian consequentialism—and social learning theory to identify cognitive mechanisms (follower other‐orientation and cognitive reflection) through which servant leadership affects employee behavior benefiting two stakeholder groups: a community nonprofit organization and the employing organization. Furthermore, we evaluate the degree to which an employee's moral identity internalization acts as a boundary condition of servant leadership's effects. Data were collected from 274 employee‐supervisor dyads across three waves with objective cognitive reflection scores and objective measures of workplace charitable giving and employee performance. Results supported all hypothesized predictions even after accounting for three alternative mediators. In particular, servant leadership had a positive indirect effect on workplace charitable giving through follower other‐orientation; it also had a positive indirect effect on objective follower financial performance through other‐orientation and cognitive reflection. Both indirect effects were significant at low levels of moral identity internalization but not at high levels. We discuss the implications of these findings and delineate directions for future research.